Implementation and Analysis of a Refactoring Tool for Detecting Code Smells - Kaur, Amandeep; Raperia, Himanshi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Software development is a field which is in action for decades. Preparing code for Software is not a difficult task, but preparing an efficient code is complicated one. To change the code is to make internal structure of the code easier to understand and economic to modify, without changing the behavior and desired response. More changes will make software patchy. No Software is free from smells especially the patchy one. Lots of work has been done for detecting and removing a few of the smells (Refactoring) from code. In this paper our main focus will be on tool SCSD (Software Code Smell Detector) developed, uses a bit classification, clustering approach with K-mean Clustering Algorithm to detect the code smells, which can implement completely different architecture if it discovers smell.Â 